Allograft Salvage Procedure in Multiple-Revision Anterior Cruciate Ligament Reconstruction. (February 2013) - Buda, Roberto; Ruffilli, Alberto; Di Caprio, Francesco; Ferruzzi, Alberto; Faldini, Cesare; Cavallo, Marco; Vannini, Francesca; Giannini, Sandro
Background: Multiple-revision anterior cruciate ligament (ACL) reconstructions represent a surgical challenge due to the presence of previous tunnels, hardware, injuries to the secondary stabilizers, and difficulties in retrieving autologous tendons. An anatomic ACL reconstruction may therefore result in a demanding surgery, thus requiring 2 stages. Purpose: To analyze the efficacy of an over-the-top ACL reconstruction technique plus extra-articular plasty using Achilles or tibialis posterior tendon allograft in restoring knee stability in patients with at least 2 failed previous ACL reconstructions, as well as to evaluate the factors able to affect the final outcome. Study Design: Case series; Level of evidence, 4. Methods: From 2002 to 2008, 24 male athletes with a mean age of 30.8 years underwent surgery. Twenty patients had undergone 2, whereas 4 patients had undergone 3 previous reconstructions. The International Knee Documentation Committee (IKDC) score and KT-2000 arthrometric evaluation were used to measure outcomes at a mean follow-up period of 3.3 years (range, 2-7). Results: The mean ± SD IKDC subjective score at follow-up was 81.3 ± 14.0. The IKDC objective score was an A or B in 20 patients (83%). Arthrometer side-to-side difference averaged 3.1 ± 1.1 mm. Range of motion was normal or nearly normal in 23 patients and abnormal in 1. Of the 20 good results, 17 patients resumed sports activity at the preinjury level. Conclusion: A 2-stage revision is an accepted option in cases of excessive tunnel enlargement and bone loss, especially on the femoral side, to achieve anatomic reconstruction. Nonanatomic over-the-top ACL reconstruction and lateral extra-articular plasty technique allow one to overcome difficult anatomic situations on the femoral side, permitting a 1-step surgery. The overall results obtained in this series are comparable with those of other ACL revision series. The higher rate of mild instability observed in our series may not be attributable to the surgical technique but rather to the chronic instability suffered by these knees before last revision.